Hyporeninemic hypoaldosteronism and diabetes mellitus: Pathophysiology assumptions, clinical aspects and implications for management - Sousa, André Gustavo P (World J Diabetes, 2016)
Patients with diabetes mellitus (DM) frequently develop electrolyte disorders, including hyperkalemia. The most important causal factor of chronic hyperkalemia in patients with diabetes is the syndrome of hyporeninemic hypoaldosteronism (HH), but other conditions may also contribute. Moreover, as hyperkalemia is related to the blockage of the renin-angiotensin-aldosterone system (RAAS) and HH is most common among patients with mild to moderate renal insufficiency due to diabetic nephropathy (DN), the proper evaluation and management of these patients is quite complex. Despite its obvious relationship with diabetic nephropathy, HH is also related to other microvascular complications, such as DN, particularly the autonomic type. To confirm the diagnosis, plasma aldosterone concentration and the levels of renin and cortisol are measured when the RAAS is activated. In addition, synthetic mineralocorticoid and/or diuretics are used for the treatment of this syndrome. However, few studies on the implications of HH in the treatment of patients with DM have been conducted in recent years, and therefore little, if any, progress has been made. This comprehensive review highlights the findings regarding the epidemiology, diagnosis, and management recommendations for HH in patients with DM to clarify the diagnosis of this clinical condition, which is often neglected, and to assist in the improvement of patient care.